2021
DOI: 10.3390/microorganisms9061171
|View full text |Cite
|
Sign up to set email alerts
|

Further Studies on the 3-Ketosteroid 9α-Hydroxylase of Rhodococcus ruber Chol-4, a Rieske Oxygenase of the Steroid Degradation Pathway

Abstract: The biochemistry and genetics of the bacterial steroid catabolism have been extensively studied during the last years and their findings have been essential to the development of biotechnological applications. For instance, metabolic engineering of the steroid-eater strains has allowed to obtain intermediaries of industrial value. However, there are still some drawbacks that must be overcome, such as the redundancy of the steroid catabolism genes in the genome and a better knowledge of its genetic regulation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…kshB is a monooxygenase widely present in steroid-degrading bacteria. It is essential to open the steroid B-ring, thereby initiating degradation of the steroid ring system [ 31 , 32 ]. In a recent study, Hsiao et al demonstrated that fadD3 gene expression was upregulated during the degradation of E1 by Rhodococcus sp.…”
Section: Resultsmentioning
confidence: 99%
“…kshB is a monooxygenase widely present in steroid-degrading bacteria. It is essential to open the steroid B-ring, thereby initiating degradation of the steroid ring system [ 31 , 32 ]. In a recent study, Hsiao et al demonstrated that fadD3 gene expression was upregulated during the degradation of E1 by Rhodococcus sp.…”
Section: Resultsmentioning
confidence: 99%
“…3-Ketosteroid 9α-hydroxylase (KSH), an essential enzyme in bacterial steroid degradation, consists of two components: a Rieske oxygenase (KshA) and a ferredoxin reductase (KshB). [75][76][77][78] It catalyzes the 9α-hydroxylation of ASD ( 8) to produce 9α-OH-ASD (43). Qin and coworkers reconstituted the NADH regeneration system, utilizing the fusion expression of toluene 2,3-oxidoreductase TDO-R from Pseudomonas putida F17 instead of KshB, along with a Rieske [2Fe-2S] iron-oxidoreductant protein, TDO-F. 79 The reconstitution significantly enhanced the electron transfer efficiency by 176.3%.…”
Section: Rieske Oxygenasesmentioning
confidence: 99%
“…Biocatalytic transformations begin with the oxidation of steroids to stenones by a cholesterol oxidase (ChOx; Baldanta et al, 2021 ; Figure 6 ). ChOx is an extracellular flavin-dependent bifunctional oxidoreductase catalyzing the oxidation of a Δ 5 -ene-3β-hydroxysterol to Δ 5 -ene-3β-ketosteroid and the isomerization of the latter to yield Δ 4 -ene-3β-ketosteroid ( Fernández de las Heras et al, 2011 , 2014 ).…”
Section: Biocatalysis Of Steroidsmentioning
confidence: 99%
“…The steroid nucleus degradation involves oxygen-dependent rupture and subsequent hydrolytic cleavage of rings A and B following the 9,10-seco pathway due to 3-ketosteroid-dehydrogenase (KstD) and 3-ketosteroid 9α-hydroxylase (KsH). AD – 4-androstene-3,17-dione; ADD – androsta-1,4-diene-3,17-dione; 9OH-AD –9α-hydroxy-4-androstene-3,17-dione; 9OH-ADD – 9 α -hydroxyandrosta-1,4-diene-3,17-dione; 3-HSA – 3-hydroxy-9,10-secoandrosta-1,3,5(10)-triene-9,17-dione; 3,4-DHSA – 3,4-dihydroxy-9,10-secoandrosta-1,3,5(10)-triene-9,17-dione; 4,9-DSHA – 4,5,9,10-diseco-3-hydroxy-5-9-17-trioxoandrosta-1(10),2-diene-4-oic acid; HIP – 3aα-H-4α (3′-propanoate)-7a-β-methylhexahydro-1,5-indanedione; OPCA – oxypentadienecarboxylic acid ( Haußmann et al, 2013 ; Kreit, 2017 ; Baldanta et al, 2021 ).…”
Section: Biocatalysis Of Steroidsmentioning
confidence: 99%
See 1 more Smart Citation